Global rotavirus vaccine introductions and coverage: 2006 – 2016 - Abou-Nader, Alice J. (Hum Vaccin Immunother, 2018)
An estimated 215,000 children died of rotavirus infections in 2013, accounting for 37% of diarrhea-related deaths worldwide, 92% of which occurred in low and lower-middle income countries. Since 2009 the World Health Organization (WHO) recommends the use of rotavirus vaccines in all national immunization programs. This review compares rotavirus vaccine (RV) introductions and vaccine coverage by region, country income status and Gavi-eligibility from 2006–2016. Gross National Income data from the World Bank and surviving infant population from United Nations Population Division was obtained for 2016. Data from WHO were collected on rotavirus vaccine coverage, national immunization schedules, and new vaccine introductions for 2016 while estimated rotavirus deaths were collected for 2013, the last year of available WHO data. As of December 2016, the majority of countries (57%, 110/194) had not introduced universal rotavirus vaccine despite WHO's 2009 recommendation to do so. Countries in the WHO African region had the greatest proportion of introductions (37%, 31/84) by December 2016 and a great majority of these (77%, 24/31) were supported by new vaccine introduction (NVI) grants from Gavi. Almost half (48%) of global introductions were in low and lower-middle income Gavi-eligible and Gavi-graduating countries. Conversely, countries in the Southeast Asia WHO region and those not eligible for Gavi NVI support have been slow to introduce rotavirus vaccine. High-income countries, on average, had poorer rotavirus vaccine coverage compared to low and lower-middle income countries. The over-representation of African countries within the Gavi subset and high estimated rotavirus deaths in these African countries, likely explains why introduction efforts have been focused in this region. While much progress has been made with the integration and implementation of rotavirus vaccine into national immunization programs, 110 countries representing 69% of the global birth cohort had yet to introduce the vaccine by December 2016.